Elasticity of the Achilles Tendon in Individuals With and Without Plantar Fasciitis: A Shear Wave Elastography Study - Pan, Weiyi; Zhou, Jiping; Lin, Yuyi; Zhang, Zhijie; Wang, Yulong (Frontiers in Physiology, 2021)
The elastic properties of the Achilles tendon (AT) are altered in local injury or other diseases and in response to changes in mechanical load. Recently, elastography has been used to evaluate variations in tendon elastic properties, mainly among healthy individuals or athletes. Therefore, this study evaluated the biomechanical changes in ATs in individuals with and without plantar fasciitis (PF). The purposes were as follows: 1) to evaluate the passive elasticity of different regions of the AT in participants with and without PF, 2) to investigate the interplay between the passive elasticity in patients with PF and pain, 3) to detect optimal cut-off points of elasticity of the AT in identifying individuals with PF, and 4) to determine the correlation between the plantar fascia thickness (PFT) and pain. This cross-sectional study included 40 participants (mean age=51±13 years). When the ankle was in a relaxed position, patients with PF experienced increased passive stiffness in AT0cm (p=0.006) and AT3cm (P =0.003), but not in the neutral position. Significant correlations were observed between pain and stiffness of AT (AT0cm r=0.489, P=0.029; AT3cm r=487, P=0.030; AT6cm r=0.471, P=0.036), but not in the PFT (P=0.557). Optimal cut-off stiffness was AT (452 kPa) in the relaxed ankle position. The plantar fascia of patients with PF was significantly thicker than that of the controls (P<0.001). Findings from the present study demonstrate that tendon stiffness is a good indicator of the clinical situation of patients with PF. Monitoring and maintaining passive tendon stiffness may provide important information for the prevention and rehabilitation of PF.